Residual Toxicity of Insecticides to Neoseiulus fallacis (Acari: Phytoseiidae) in Apples - Raja Jamil, Raja Zalinda; Vandervoort, Christine; Wise, John C; Munyaneza, Joseph (Oxford University Press, 2019)
Neoseiulus fallacis (Garman) is a predatory mite that is common in apple orchards and distributed throughout North America. However, N. fallacis may be susceptible to pesticides used for the management of crop pests. This study aimed to evaluate the temporal effects of commonly used insecticides on N. fallacis survival. Neoseiulus fallacis adults were exposed to field-aged residues, and mortality and lethal time were measured over 96 h of exposure. Carbaryl caused high mortality to N. fallacis and the shortest lethal time values (LT50), followed by spinetoram, with moderate lethal time values. Esfenvalerate, acetamiprid, chlorantraniliprole, and novaluron showed little to no lethality to N. fallacis following exposure to dry field-aged residues. The results of this study provide important field-relevant knowledge that is often void from laboratory-based studies, which can aid integrated pest management (IPM) decision-makers in apple production systems. © 2019 The Author(s). Published by Oxford University Press on behalf of Entomological Society of America. All rights reserved.